# Prove that for {n}ge{2},{2}cdot{left(begin{matrix}{n}{2}end{matrix}right)}+{left(begin{matrix}{n}{1}end{matrix}right)}={n}^{2}

Question
Prove that for $${n}\ge{2},{2}\cdot{\left(\begin{matrix}{n}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{n}\\{1}\end{matrix}\right)}={n}^{2}$$

2021-01-11
Prove that for
$${n}\ge{2},{2}\cdot{\left(\begin{matrix}{n}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{n}\\{1}\end{matrix}\right)}={n}^{2}$$
Step 1. Definitions
Definition combination
$${n}{C}{r}={\left(\begin{matrix}{n}\\{r}\end{matrix}\right)}=\frac{{{n}!}}{{{r}!{\left({n}-{r}\right)}!}}$$
with $$n!=n\times(n-1)\times\dotsb\times2\times1$$.
Pascal's equation
$${\left(\begin{matrix}{n}+{1}\\{k}\end{matrix}\right)}={\left(\begin{matrix}{n}\\{k}\end{matrix}\right)}+{\left(\begin{matrix}{n}\\{k}-{1}\end{matrix}\right)}$$
Step 2. Solution
To proof: $${2}\cdot{\left(\begin{matrix}{n}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{n}\\{1}\end{matrix}\right)}={n}^{2}$$ for all positive integers.
Proof by induction
Let P(n) be the statement "$${2}\cdot{\left(\begin{matrix}{n}\\{1}\end{matrix}\right)}{\left(\begin{matrix}{n}\\{1}\end{matrix}\right)}={n}^{2}$$".
Basis step n=2
$${2}\cdot{\left(\begin{matrix}{n}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{n}\\{1}\end{matrix}\right)}={2}\cdot{\left(\begin{matrix}{2}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{2}\\{1}\end{matrix}\right)}={2}\cdot{1}+{2}={4}$$
$$n^{2}=2^{2}=4$$
Thus P(2) is true.
Inductive step. Let P(k) be true.
$${2}\cdot{\left(\begin{matrix}{k}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{k}\\{1}\end{matrix}\right)}={k}^{2}$$
We need to proof that P(k+1) is true.
$${2}\cdot{\left(\begin{matrix}{k}+{1}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{k}+{1}\\{1}\end{matrix}\right)}$$ $$={2}\cdot{\left({\left(\begin{matrix}{k}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{k}\\{1}\end{matrix}\right)}\right)}+{\left(\begin{matrix}{k}+{1}\\{1}\end{matrix}\right)}\ \text{Pascal's identity}$$
$$={2}\cdot{\left(\begin{matrix}{k}\\{2}\end{matrix}\right)}+{2}{\left(\begin{matrix}{k}\\{1}\end{matrix}\right)}+{\left(\begin{matrix}{k}+{1}\\{1}\end{matrix}\right)}\ \text{Distributive property}$$
$$={2}\cdot{\left(\begin{matrix}{k}\\{2}\end{matrix}\right)}+{\left(\begin{matrix}{k}\\{1}\end{matrix}\right)}+{\left(\begin{matrix}{k}\\{1}\end{matrix}\right)}+{\left(\begin{matrix}{k}+{1}\\{1}\end{matrix}\right)}$$
$$={k}^{2}+{\left(\begin{matrix}{k}\\{1}\end{matrix}\right)}+{\left(\begin{matrix}{k}+{1}\\{1}\end{matrix}\right)}\ \text{Since P(k) is true}$$
$$={k}^{2}+{k}+{k}+{1},\ {\left(\begin{matrix}{m}\\{1}\end{matrix}\right)}={m}$$
$$={k}^{2}+{2}{k}+{1}\ \text{Combine like terms}$$
$$=={\left({k}+{1}\right)}^{2},\ {\left({a}+{b}\right)}^{2}={a}^{2}+{2}{a}{b}+{b}^{2}$$
Thus P(k+1) is true.
Conclution. By the principle of mathematical induction, P(n) is true for all positive integers n.

### Relevant Questions

Prove that $$\displaystyle\sum_{i=1}^{n} \left(\begin{array}{c}i\\ 2\end{array}\right)=\left(\begin{array}{c}n+1\\ 3\end{array}\right)$$
$$\forall n\geq2$$
You need to prove that question
$$\displaystyle{\int_{{0}}^{{1}}} \sin{{\left(\pi{m}{x}\right)}} \sin{{\left(\pi{n}{x}\right)}}{\left.{d}{x}\right.}={\left\lbrace{\left(\begin{matrix}{0}{m}\ne{n}\\{1}\text{/}{2}{m}={n}\end{matrix}\right)}\right.}$$
Prove that $$\displaystyle\sum_{j=1}^{n} 2^{j}=2^{n+1}-2$$
$$\forall\geq1$$
A population of N =16 scores has a mean of p = 20, After one score is removed from the population, the new mean is found to be $$\displaystyleμ={19}$$. What is the value of ine score that was removed? (Hint: Compare the val- ues for X before and after the score was removed.)
Let the sequence of events E1, E2, . . . , En be independent, and assume that $$\displaystyle{P}{\left({E}{i}\right)}=\frac{{1}}{{{i}+{1}}}$$. Show that $$\displaystyle{P}{\left({E}{1}∪···∪{E}{n}\right)}=\frac{{n}}{{{n}+{1}}}$$
Enter the expression that would produce the answer (do include the answer) for row 1 column 1 of the multiplied matrix $$A \cdot B$$:
List the expression in order with the original values using $$\cdot$$ for multiplication.
then find $$A \cdot B$$
If $$A=\begin{bmatrix}3 & 7 \\2 & 4 \end{bmatrix} \text{ and } B=\begin{bmatrix}-3 & 6 \\4 & -2 \end{bmatrix}$$
Let $$\displaystyle{B}=\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{1}\backslash-{2}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace},{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}\backslash{1}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace}{\quad\text{and}\quad}{C}=\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}\backslash{1}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace},{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{1}\backslash{3}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace}$$ be bases for R^2. Find the change-of-coordinate matrix from B to C.
The coefficient matrix for a system of linear differential equations of the form $$\displaystyle{y}^{{{1}}}={A}_{{{y}}}$$ has the given eigenvalues and eigenspace bases. Find the general solution for the system.
$$\displaystyle{\left[\lambda_{{{1}}}=-{1}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{1}{0}{3}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace},\lambda_{{{2}}}={3}{i}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}-{i}{1}+{i}{7}{i}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace},\lambda_{{3}}=-{3}{i}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}+{i}{1}-{i}-{7}{i}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace}\right]}$$
The coefficient matrix for a system of linear differential equations of the form $$y^1=Ay$$
$$\lambda_1=2i \Rightarrow \left\{ \begin{bmatrix}1+i\\ 2-i \end{bmatrix} \right\} , \lambda_2=-2i \Rightarrow \left\{ \begin{bmatrix}1-i\\ 2+i \end{bmatrix} \right\}$$
$$\displaystyle{\left[\begin{matrix}{1}&{0}&-{1}&-{2}\\{0}&{1}&{2}&{3}\end{matrix}\right]}$$